EFFECTIVE DIDACTIC TOOLS AND TECHNOLOGIESFOR DEVELOPING INDEPENDENT THINKING IN“COURSE CHOICE” LESSONS - Qodirova Nilufar Abdusattor qizi (Euro Asian Journal Publishing, 2025)
It is aimed at solving the current problems of the education system of Uzbekistan, preparing the younger generation for an independent and conscious choice of profession. The article identifies indicators of independent thinking of regional students in choosing a profession, based on the strategy "Digital Uzbekistan - 2030", Dewey's pragmatism and Vygotsky's theory, as well as educational technologies
Keywords: Digital Uzbekistan; 2030" strategy; Dewey pragmatism